Chapter Boccaccio, il Decameron e la Crusca: le fonti spogliate dagli Accademici - Canneti, Caterina (Studi e saggi, 2020)
This survey concerns the lexicographic presence of Giovanni Boccaccio's Decameron in the Vocabolario of the Accademici della Crusca (from the first to the fourth edition). Boccaccio is the author that counts 15.600 occurrences (considering also his others literary works) already in the first edition. This is a significant situation about Decameron, because we know that a lot of its passages went through modifications and censorship: all of these interventions on Boccaccio's text would have had some influence on the quotations into the Vocabolario. Starting from the declarations of the Accademici, the study wants to investigate about the employment of Decameron's sources during the works for the Vocabolario, involving editions, manuscripts and Accademici's autograph papers.